الیکٹرانک ٹرانزیکشن میں جدید الیکٹرانک ذرائع کا استعمال: فقہاء اربعہ کی آراء کی روشنی میں: The Sharīʿah Point of View About New Technology Sources in E Transactions - Dr. Hafiz Muhammad Asif Javeed (Al Manhal Research Journal, 2023)
This study provides a comprehensive jurisprudential analysis of the use of modern electronic means in electronic transactions, with a particular focus on their compatibility with Islamic principles. The research explores the perspectives of the four major schools of Islamic thought—Hanafi, Maliki, Shafi'i, and Hanbali—on the permissibility and application of such transactions in light of Shari'ah.Electronic transactions, including online banking, e-commerce, digital currencies, and mobile wallets, have become integral to modern financial systems. However, their compliance with Islamic jurisprudence raises significant questions regarding issues such as riba (interest), gharar (uncertainty), and fraud prevention. This study examines these concerns while highlighting the adaptability of Islamic law to contemporary challenges. The Hanafi perspective emphasizes contractual agreements and their legal validity in digital contexts. The Maliki school focuses on customary practices (urf) and their role in legitimizing new methods of trade. Shafi'i jurisprudence addresses the conditions of contracts and digital possession, while Hanbali scholars evaluate the principles of ease and facilitation in modern transactions.The research also investigates the role of trust, transparency, and ethical considerations in electronic transactions, offering practical solutions rooted in Islamic ethics. Issues like the use of cryptocurrency, digital signatures, and online dispute resolution are analyzed under Shari'ah principles. By synthesizing classical Islamic jurisprudence with modern financial practices, this study seeks to provide a framework for Muslims to engage with electronic transactions confidently and in compliance with their faith. The findings aim to bridge the gap between tradition and technology, offering guidance for scholars, practitioners, and users alike.